2017
DOI: 10.1002/ajim.22717
|View full text |Cite|
|
Sign up to set email alerts
|

Lung function not affected by asbestos exposure in workers with normal Computed Tomography scan

Abstract: Our results confirm the well-known correlation between lung function, smoking habits, and BMI. However, we found no significant association between lung function and asbestos exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In the present study, D LCO /VA was not sensitive, confirming the results of van der Lee et al [36] and Hughes & Pride [37] where the transmission coefficient D LCO / VA had no diagnostic added value compared to the parameters D LCO and VC for the detection of diffuse parenchymal diseases. In accordance, Schikowsky et al [38] showed no impairment of D LCO /VA and no reduction in VC in subjects formerly exposed to asbestos. In difference, the D LCO results were not presented.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, D LCO /VA was not sensitive, confirming the results of van der Lee et al [36] and Hughes & Pride [37] where the transmission coefficient D LCO / VA had no diagnostic added value compared to the parameters D LCO and VC for the detection of diffuse parenchymal diseases. In accordance, Schikowsky et al [38] showed no impairment of D LCO /VA and no reduction in VC in subjects formerly exposed to asbestos. In difference, the D LCO results were not presented.…”
Section: Discussionsupporting
confidence: 70%
“…Another study used a study design similar to ours to compare respiratory function test by cumulative exposure to asbestos, among subjects exposed to 49 f/mL-year on average, a level more than 10 times higher than that experienced by our study subjects. After excluding subjects with an abnormal CT scan, there was no correlation between cumulative exposure or duration of exposure, and lung function parameters and airways resistance [23].…”
Section: Discussionmentioning
confidence: 85%
“…New HRCT findings are revealing additional imaging characteristics important to the diagnosis of occupational lung disease [67][68][69][70]. A negative chest CT also proves useful in excluding disease [71]. The International Classification of High-Resolution Computed Tomography for Occupational and Environmental Respiratory Diseases recently demonstrated correlation with physiologic testing [72].…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%